Change of fracture mode in CVN toughness transition temperature range - Vodopivec, Franc (Kovine zlitine tehnologije, 1999)
Survey of ref. data on CVN fracture. Tensile and CVN tests on structural steels with yield stress 372 to 737 MPa and different microstructure in temperature interval +22°C to NDT -20°C. Tensile and CVN fracture surface micromorphology. Increase of CVN ductile fracturing temperature because of deformation generated heat. Reduction of area, CVN toughness in transition temperature range, and crack tip blunting. Change of fracture mode by fracturing of CVN specimens in transition temperature range.
Keywords: jekla; mehanske lastnosti; žilavost; mikrostruktura